Pemanfaatan Biochar Sekam Padi, Tongkol Jagung dan Cangkang Kelapa untuk Meningkatkan Produksi Bawang Merah (Allium cepa) - Zamzam, Syamsiar; Rahim, Abd.; Nurbaya,; Syamsinar, (Journal Galung Tropika, 2024)
Agricultural waste becomes a major post-harvest problem if not processed correctly. Post-harvest agricultural waste processing into biochar can be the right post-harvest handling solution and can be used to improve soil nutrient structure. This study aimed to determine the use of agricultural waste biochar to increase shallot production. This study was in the form of an experiment using a Randomized Block Design (RAK) with treatments including rice husk biochar (BSP), corn cob biochar (BTJ), coconut shell biochar (BCK), rice husk biochar + corn cob biochar (BSP + BTJ), rice husk biochar + coconut shell biochar (BSP + BCK), corn cob biochar + coconut shell biochar (BTJ + BCK), and rice husk biochar + corn cob biochar + coconut shell biochar (BSP + BTJ + BCK). The results showed that using rice husk biochar, corn cob, and coconut shell individually or in combination could increase shallot production. The highest output of shallots was demonstrated in the treatment of rice husk biochar + corn cob biochar + coconut shell biochar.